PEMBERDAYAAN MASYARAKAT TANI MELALUI PELATIHAN MINI GARDEN DI DESA TELAGA LUHUR - Dewi Surani; Dina Awaliyah; Nova Novianti; Emil Bari Sohibul Ulum; Kurniawati Kurniawati (National Conference on Applied Business, Education, & Technology (NCABET), 2021)
Reforestation is one of the important activities that must be implemented conceptually in dealing with environmental crises. Telaga Luhur Village, Waringin Kurung Sub-district, Serang-Banten is one of the villages that is quite active in supporting reforestation programs. In an effort to save the environment, the community together with relevant stakeholders have carried out various reforestation activities. The activity aims to examine how the form of community involvement in reforestation efforts in the Sidilem village area. The community has actually been involved in the process of planning, providing, maintaining, and supervising reforestation activities. However, the community considers that the condition of green space in Sidelem village is currently very minimal. Reforestation activities are carried out with various objectives, including: to add ecological value, add aesthetic value, obtain economic benefits, as well as reasons to support government programs. The presence of stakeholders consisting of the City Government, Village Government, Non-Governmental Institutions, Private/CSR, and Community/Academics has contributed greatly to the development of reforestation activities in the service area